The job security as a factor of integration of non-EU foreign workers. - Charro Baena, Pilar (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The present study has tried to prove that the principle of employment stability is a legal condition of the employment contract; because of this it is an aspect of which must be respected in all work relations with foreign workers. In application of the aforementioned principle, after having examined the different kinds of work permits and their possible link with an employment contract, the erroneous connection made between the temporary nature of work permits and the temporary nature of the signed contracts by foreign workers is condemned.